Performance Evaluation of Alkaline Activated Geopolymer Binders Using RCA and Industrial By-Products as Cement Alternatives - Shaaban, Mostafa; Edris, Walid Fouad; Al Sayed, Abd Al-Kader A.; Alrashidi, Raid S.; Selouma, Tarek Ibrahim (Salehan Institute of Higher Education, 2025)
This study explores the performance of alkaline-activated geopolymer binders using industrial by-products and recycled concrete fine aggregate (RCFA) as sustainable alternatives to traditional cement. Materials such as granulated blast furnace slag (GBFS), silica fume (SF), red brick powder (RBP), quick lime (QL), and RCA were utilized to develop eco-friendly binders with enhanced mechanical and durability properties. Experimental tests evaluated physical, mechanical, and microstructural characteristics, including setting times, dry density, flexural strength, and compressive strength. Advanced analysis with SEM and EDAX examined aggregate-binder bonding. Results highlighted the critical role of binder composition in determining performance. Balanced mixtures of GBFS, SF, and RBP achieved superior strength, durability, and compact microstructures, while excessive QL increased porosity, reducing effectiveness. Optimal flexural strength (4.24 MPa at 56 days) was observed for the G30/S40-L20 formulation, underscoring the importance of precise proportions. Composition influenced setting times, with SF delaying gelation and high QL content accelerating it. The findings demonstrate the viability of using RCFA and industrial by-products in sustainable construction, offering a pathway to reduce reliance on traditional cement. The study emphasizes optimizing binder formulations for strength and durability while addressing environmental impacts, encouraging further research into long-term performance under diverse conditions. This innovative approach highlights the potential for integrating recycled and industrial by-products into construction practices to achieve eco-friendly solutions and promote sustainable urban development. Doi: 10.28991/CEJ-2025-011-02-018 Full Text: PDF